(untitled) (Training and Practice : Journal of Educational Sciences, 2019)
The goal of my research is to increase the efficiency of education by finding and examining methods that improve the physical, psychical and mental state of the students. Based on research results on psychophysical state of the students, particularly on anxiety and stress, I studied methods that can improve students’ mental state in a contact classroom environment. Among the methods suitable to improve the mental state I chose longer relaxation in lying position lasting one hour. The examination of the effects of shorter relaxation in upright position at the beginning, during and at the end of the lesson is the subject of a subsequent research. As the theoretical background of the research, I chose the theory of cognitive load. Among the various approaches to cognitive load, I chose the most recent variant using the term of generative resources. This new version of cognitive load theory provides an opportunity to use relaxation as a mean to reduce stress and anxiety thus increasing generative resources and improving the efficiency of learning. After a brief summary of literature about the generative resources and relaxation, the results of the research will be discussed in details. In the pre research I analyzed by semi-structured interviews, reports and questionnaires the methods and effects of the program Nr. 27282/162/2016 accredited by the National Agency for Vocational and Adult Education aiming at the development of physical, psychical and mental health by reducing anxiety and stress. The study was conducted mainly on the lecturers and students of the Faculty of Primary and Pre-School Education of the Eötvös University and Ybl Miklós Civil Engineering Faculty of Szent István University. After the detailed description of the results further research plans and opportunities will be presented. Among the experiences, it should be emphasized that the activity in this area is much higher than expected, which is a good basis for further theoretical and practical research. Based on the experience gained in the study of contact classroom education, I will examine the efficiency gains of similar methods that can be applied in the distance learning environment using empirical methods with psychophysical sensors such as ECG, EEG, skin resistance and skin temperature gauge. The main purpose of a further study is to examine the methods that could be included in practice of instructional design, using for example the Nexius model.